A lethal skeletal dysplasia with features of chondrodysplasia punctata and osteogenesis imperfecta: an example of Astley-Kendall dysplasia. Further delineation of a rare genetic disorder. Issue 6 (June 1998) - Elçioglu, N; Hall, C M
Abstract : An unusual osteochondrodysplasia presenting with lethal neonatal short limbed dwarfism, defective ossification, and punctate calcification within cartilage is presented. The features resemble four cases previously described with Astley-Kendall dysplasia.